The Theory, Objective and Function of The Monetary Policy - Kakhorova Anora Nusratovna (European Science Publishing, 2023)
This article comprises a study of monetary policy in Uzbekistan and analyzes the potential channels of monetary policy transmission mechanism as a vehicle to evaluate the efficiency of monetary policy. The research is rather compelling of the accomplishment of monetary policy in Uzbekistan, especially in rates of exchange, reserve prerequisites, interest rate, inflation targeting. The goal of this article to observe whether the monetary instruments impact on the economy of Uzbekistan. We have investigated the importance and role of the monetary policy in Uzbekistan.
Keywords: Monetary policy, economic growth, exchange rate, inflation, mechanism.